Followership and the Relationship Between Kelley’s Followership Styles and the Big Five Factor Model of Personality - Kudek, Donald R.; Winston, Bruce; Wood, James Andy (Journal of Organizational Psychology, 2020)
This research determined the relationship between an individual’s personality traits and followership characteristics. Using Kelley’s Followership Questionnaire, which measures active engagement and independent thinking, and the Mini-International Personality Item Pool (IPIP) personality test, which measures Big Five personality levels of extraversion, neuroticism, agreeableness, conscientiousness, and openness to experience, we collected data from 238 full-time working adults in the United States. The data indicates a positive relationship between the personality characteristics of extraversion, agreeableness, conscientiousness, and openness to experience with the followership attributes of active engagement and independent thinking. Neuroticism was negatively correlated to both active engagement and independent thinking.